Predicting the retention of first-time donors using an extended theory of planned behavior - Masser, B.; Bednall, T.; White, K.; Terry, Deborah (Wiley-Blackwell, 2012)
BACKGROUND: Donor retention is vital to blood collection agencies. Past research has highlighted the importance of early career behavior for long-term donor retention, yet research investigating the determinants of early donor behavior is scarce. Using an extended Theory of Planned Behavior (TPB), this study sought to identify the predictors of first-time blood donors' early career retention. STUDY DESIGN AND METHODS: First-time donors (n = 256) completed three surveys on blood donation. The standard TPB predictors and self-identity as a donor were assessed 3 weeks (Time 1) and at 4 months (Time 2) after an initial donation. Path analyses examined the utility of the extended TPB to predict redonation at 4 and 8 months after initial donation. RESULTS: The extended TPB provided a good fit to the data. Post-Time 1 and 2 behavior was consistently predicted by intention to redonate. Further, intention was predicted by attitudes, perceived control, and self-identity (Times 1 and 2). Donors' intentions to redonate at Time 1 were the strongest predictor of intention to donate at Time 2, while donors' behavior at Time 1 strengthened self-identity as a blood donor at Time 2. CONCLUSION: An extended TPB framework proved efficacious in revealing the determinants of first-time donor retention in an initial 8-month period. The results suggest that collection agencies should intervene to bolster donors' attitudes, perceived control, and identity as a donor during this crucial post–first donation period.